Pengaruh Temperatur Dan Waktu Pengovenan Tulang Sapi Timor Terhadap Hasil Uji FTIR - Melian, Makxy Melian; Adoe, Dominggus G. H.; Maliwemu, Erich U. K. (Universitas Nusa Cendana, 2024)
This study evaluates the effect of temperature and oven time on the results of the Fourier Transform Infrared Spectroscopy (FTIR) test on Timorese cow bones. Beef bones from East Nusa Tenggara, which are rich in calcium and phosphorus, are processed through cleaning, boiling, and soaking H2O2 before calcining at various temperatures (100°C, 200°C, 300°C) and duration (1 and 2 hours). The FTIR results showed significant changes in the chemical structure of the bones, with variations in temperature and baking time affecting the quality and characteristics of the bones. The study concluded that the precise setting of the ovening parameters can improve the quality of beef bone-based products, such as hydroxyapatite.